The effect of college degree attainment on neurodegenerative symptoms in genetically at-risk women. (September 2022) - Hong, Jinkuk; Dembo, Robert S.; DaWalt, Leann Smith; Brilliant, Murray; Berry-Kravis, Elizabeth M.; Mailick, Marsha
Abstract: Using longitudinal data, the present study examined the association between college degree attainment and the manifestation of neurodegenerative symptoms among women (n = 93) at elevated genetic risk. The neurodegenerative symptoms investigated in this study are due to FXTAS (Fragile X-associated Tremor/Ataxia Syndrome), a condition with onset after age 50. Those at risk for FXTAS have a mutation of a single gene found on the X chromosome. FXTAS is characterized by intention tremor, gait ataxia, executive function deficits, memory issues, and neuropathy. College degree attainment has been shown to provide neuroprotective effects in the general population, delaying the development of neurodegenerative conditions such as Alzheimer's disease. For this reason, college degree attainment is a potentially salient resource for those at risk of FXTAS. The results of the present research indicated significantly more severe FXTAS symptoms in women who did not attain a college degree as compared with those who were college graduates, although the two groups were similar in age, genetic risk, household income, health behaviors, and general health problems. Furthermore, symptoms in those who did not attain a college degree worsened over the 9-year study period at a significantly faster rate than the college graduates. The association between college degree attainment and FXTAS symptoms was significantly mediated by depression, which was lower among the graduates than those who did not attain a college degree. Thus, the present research is an example of how a sociodemographic factor can mitigate neurodegenerative conditions in genetically at-risk adults. Highlights: Neurodegenerative effects of X chromosome mutation are reduced by college education. 9-year longitudinal study reveals that college education mitigates genetic risk. 1 in 150 women have the FMR1 premutation, with risk for neurodegenerative symptoms. Cognitively enriching experiences can be neuroprotective via improved mental health.